Modern Tendences of the Development of the System of Music-Rhythmic Education of Junior Schoolchildren - Poliakova, Anastasiia (Pedagogical Discourse, 2017)
The article analyzes the main points of the conceptions of musical and rhythmic education which are reflected in the researches by E. Jaques-Dalcroze, K. Storck, K. Orff, B. Teplov and others. We look at the tendencies of the development of musical and rhythmic education system of primary school pupils in the present period (N. Vetlugina, T. Sirotina, G. Bezvinenko, O. Koval, O. Lobova). We identify areas of pedagogical work to refresh the content, develop organizational and methodological principles of musical and rhythmic education of pupils and provide them with aesthetic and creative development at music lessons in school. One of leading ideas of muzichno-pedagogichnoy education of junior schoolboys is based on that a rhythm comes forward the important constituent of musical education, as most naturally represents the necessity of students to realize the pictures of musical space and time, appearance and maintenance, by various motions, kinds musically motive to activity. Consideration of the last tendencies in industry musically rhythmic education of junior schoolboys with the purpose of certain update of his maintenance and development of pedagogical approaches, organizationally methodical principles of pedagogical work in this direction, to our opinion, have an important value in the modern terms of development of artistic education. Musically rhythmic abilities of schoolboys can effectively develop on the lessons of music (in the process of study of songs, listening of music), and also in extracurricular to musically educate to work (preparation of school measures, staging of songs, musically playing activity, choreography) In addition rhythmic motions to music are instrumental in strengthening of child’s organism, develop motoriku and co-ordination, enrich emotionally practical experience of perception of different pieces of music, to the awareness of them genre-stylish, artistic expression.